O uso de sequências didáticas como recurso metodológico para o ensino de matemática no ensino fundamental II - Maia, Raul Moésio Lima (Universidade Federal Rural do Semi-Árido, 2020)
The present study reflects on the use of Didactic Sequences as methodological proposals in the teaching and learning process of Mathematics. Therefore, we intend with this work to reframe and search for alternatives that can help the teacher in the teaching process of some Mathematics contents, as well as investigate possibilities to structure Didactic Sequences for this purpose, seeking innovative practices that contribute efficiently to the challenges encountered currently in math classes. We are based on qualitative research, in which we chose bibliographic research, where the referentials that support the study were synthetically reconstructed. Then, we elaborate the activities that will constitute the Didactic Sequences. The contents chosen to be worked on were: Potentiation and Radication, Area and Perimeter, Fractions and Pythagorean Theorem. We chose these subjects because we realized, during our teaching experience, that the learning difficulties of these contents are recurrent. We believe that from the elaboration of a Didactic Sequence we will be able to present students with significant situations so that they can interact and better understand Mathematics. We hope that the Didactic Sequences elaborated and the bibliographic reference here reconstituted not only helps teachers, but also contributes to the development of their own Didactic Sequences, thus collaborating for the teaching and learning of the discipline. It is in this context that we conceive the idea that the provision of continuing education for mathematics teachers is configured as a fundamental activity, since it can be an articulator of scientific knowledge of mathematics with the didactic aspect
Keywords: Sequência Didáticas; Ensino e aprendizagem de Matemática; Formação continuada de Professores; Didactic Sequence; Teaching and learning of Mathematics; Continuing Teacher Education; CIENCIAS EXATAS E DA TERRA::MATEMATICA